On the Philosophy that Should Not Be - Gironi, Fabio (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Fabio Gironi Title (English): On the Philosophy that Should Not Be Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 118-120 Page Count: 3 Citation (English): Fabio Gironi, “On the Philosophy that Should Not Be,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 118-120.